Helping the Students' Difficulties in Learning Islamic Education Subject by Implementing Jigsaw Cooperative Learning Strategy at SMA Ar-Rahman Medan Helvetia - Harahap, Abdi Syahrial; Ependi, Rustam; Harahap, Muhammad Yunan; Katresna, Sekar (Proceeding International Conference on Malay Identity, 2024)
This study aimed to find an effective solution in improving learners' understanding of Islamic Religious Education through the application of the Jigsaw cooperative learning model. This case study was relevant because it can provide valuable insights into how to overcome students' learning difficulties and improve the quality of Islamic learning in high school education. The subject of this reseacrh was ten students who was taught by using the jigsaw learning strategy. The teachers conducted a curriculum analysis to determine the competency standards and basic competencies that would be delivered to students using this model. Students' learning outcomes in the subject of Islamic Education were classified as Good, with an overall average percentage of 71 falling within the 66-79 interval. The improvement in student learning outcomes from Cycle I to Cycle II suggested that the implemented improvements in teaching could address the challenges faced. The Jigsaw approach can enhance collaboration among students, allowing them to share knowledge and understanding of various aspects of Islamic Education. By dividing the lesson material into small parts, each student takes responsibility to understand and teach a specific part. The implication of this research underscores the importance of implementing appropriate learning approaches tailored to students' characteristics, such as Jigsaw, to enhance their understanding of PAI subjects, particularly for students facing learning difficulties.